Article review for Acta Musicologica - Assis, Paulo de (2023)
Mario Bertoncini’s Spazio-Tempo (1970): Reading between the lines of an unwritable scoreThe theatrical-installative work Spazio-Tempo (1970) by the Italian composer Mario Bertoncini (Rome, 1932 – Siena, 2019) offers us the occasion to explore “the positive function of notation” within the creative process, as presented by Emily Payne and Floris Schuiling. Payne and Schuiling understand notation “not as the representation of an abstract structure but as a concrete material object, in order to move beyond a paradigm that opposes notated permanence to performed and/or improvised transience.” Thus, using the case of Spazio-Tempo, I will explore the creative process and scoring materials through an examination of both the work’s written traces and its unwritten practices. In the case of Bertoncini and Spazio-Tempo, these unwritten practices are to be found in the knowledge and exercises developed and embodied by Bertoncini as a member of the Rome-based improvisation collective Gruppo di Improvvisazione Nuova Consonanza (GINC from now on), in which Bertoncini participated from 1965. In particular, I will discuss whether these unwritten elements of GINC’s improvisation practice at the time–the development of which relies heavily on Bertoncini’s input–percolated into Bertoncini’s personal creative process, whether they have prescriptive power, and whether they can fill the gaps present between the lines of the written scoring materials of Spazio-Tempo.This article appropriates Payne and Schuiling’s questions as the most cogent framing through which Spazio-Tempo can be understood: “Is it possible to describe how scores can function as sources of creative knowledge for performers, while avoiding the discourse of ‘reproduction’[…]? Moreover, can notation be understood not just as an object of cognition, but as an integral element of the forms of social and creative interactions that are now seen to characterize performance?” Or, more specifically: to what extent does collective improvisation practice ripple into individual composition practice? And how can we use the knowledge developed in this collective practice to navigate a notational environment usually described as “indeterminate”? Through a close reading of the archival materials and the use of the embodied knowledge Bertoncini developed while participating in the GINC, I will argue that, instead of wondering what actions Bertoncini expected the instrumentalists to produce, we should ask what skills he expected them to have.
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music